Antimicrobial activity of bovine lactoferrin against Gardnerella species clinical isolates - Pino, Alessandra; Mazza, Tommaso; Matthews, Maura-Ann H.; Castellana, Stefano; Caggia, Cinzia; Randazzo, Cinzia L.; Gelbfish, Gary A. (Frontiers in Microbiology, 2022)
Gardnerella species play a key role in the development and recurrence of Bacterial Vaginosis (BV), a common imbalance of the vaginal microbiota. Because of the high rates of BV recurrence reported after treatment with standard of care antibiotics, as well as the emergence of antibiotic-resistant BV, the development of alternative treatment approaches is needed. Bovine lactoferrin, a well studied iron-binding glycoprotein with selective antimicrobial activity, may ameliorate vaginal dysbiosis either alone or in combination with antibiotics. The present study evaluated the antimicrobial resistance/susceptibility profile of seventy-one presumptive G. vaginalis clinical isolates to metronidazole and clindamycin. In addition, the in vitro antimicrobial activity of Metrodora Therapeutics bovine Lactoferrin (MTbLF) against the tested clinical isolates, both alone and in combination with metronidazole and clindamycin, was in depth evaluated using defined-iron culture conditions. All 71 presumptive G. vaginalis clinical isolates exhibited resistance to metronidazole, with MIC values greater than 256 µg/ml. Different susceptibility profiles were detected for clindamycin. In detail, the vast majority of the tested strains (45%), exhibiting MIC lower than 2 µg/ml, were considered sensitive; eighteen strains (25%) with MIC higher or equal to 8 µg/ml, were classified as resistant, whereas the remaining 21 (30%) were classified as intermediate. MTbLF was tested in culture medium at different concentrations (32 mg/ml, 16 mg/ml, 8 mg/ml, 4 mg/ml, 2 mg/ml, 1 mg/ml, and 0.5 mg/ml) showing ability to inhibit the growth of the tested presumptive G. vaginalis clinical isolates, including those metronidazole-resistant, in a dose-dependent and not in a strain-dependent manner. MTbLF, at concentrations ranging from 32mg/ml to 8mg/ml, exerted a statistically different antimicrobial activity compared with lower concentrations (4 mg/ml, 2 mg/ml, 1 mg/ml, and 0.5 mg/ml). A synergistic effect between MTbLF (8mg/ml and 4mg/ml) and clindamycin was revealed for all the tested strains. When tested in the absence of other sources of iron, MTbLF did not support the growth of the tested presumptive G. vaginalis clinical isolates. Bovine lactoferrin may be a potential candidate to treat Gardnerella species infection.